2022
DOI: 10.3390/biomedicines10020299
|View full text |Cite
|
Sign up to set email alerts
|

PBK/TOPK Is a Favorable Prognostic Biomarker Correlated with Antitumor Immunity in Colon Cancers

Abstract: Immune checkpoint inhibitor therapy has proven efficacy in a subset of colon cancer patients featuring a deficient DNA mismatch repair system or a high microsatellite instability profile. However, there is high demand for more effective biomarkers to expand the colon cancer population responding to ICI therapy. PBK/TOPK, a serine/threonine kinase, plays a role in cell cycle regulation and mitotic progression. Here, we investigated the correlation between PBK/TOPK expression and tumor immunity and its prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Additionally, PBK promotes metastasis and resistance to oxaliplatin by regulating pathways such as ETV4-uPAR and PTEN in hepatocellular carcinoma [ 47 , 48 ]. The prognostic value of PBK in prediction of survival and antitumor immunity was also proved in colorectal cancer [ 49 51 ]. Therefore, the prognostic CRs identified in our study also exert fundamental role in various cancers and have potential to be reliable survival predictor and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PBK promotes metastasis and resistance to oxaliplatin by regulating pathways such as ETV4-uPAR and PTEN in hepatocellular carcinoma [ 47 , 48 ]. The prognostic value of PBK in prediction of survival and antitumor immunity was also proved in colorectal cancer [ 49 51 ]. Therefore, the prognostic CRs identified in our study also exert fundamental role in various cancers and have potential to be reliable survival predictor and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…The PBK is a novel serine/threonine kinase that is highly expressed in proliferating cells and tissues [ 51 ]. A recent study demonstrated a negative correlation between PBK expression and immune suppressor cells, including regulatory T cells and M2 macrophages [ 52 ]. Moreover, Zhu et al [ 53 ] found that PBK expression was suppressed after the development of inflammation in thin endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…found that TOPK could influence the level of immune cell infiltration in colon cancer. 19 Moreover, Tingting Feng et al. found that TOPK was associated with T cell function infiltrating in RCC by bioinformatics, suggesting that TOPK may affect immune evasion in RCC, although the exact mechanism is unknown.…”
Section: Introductionmentioning
confidence: 99%